Epidemiological features of tuberculosis infection in a high-altitude population: a population-based, cross-sectional survey in Tibet, China - Wang, Jian; Pei, Shaojun; Yang, Guofeng; Qucuo, Nima; Song, Qifei; Liu, Xiaoqiu; Li, Xue; Chen, Wei; Li, Tao; Liu, Eryong; Ou, Xichao; Chen, Hui; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTargeted strategies for marginalized populations, including high-altitude communities, are crucial for TB elimination. This study assessed TB infection (TBI) prevalence across altitudinal gradients and evaluated altitude-dependent risk factors in Tibet, China.MethodsA cross-sectional survey by multistage stratified random cluster sampling was conducted using ESAT6-CFP10 skin test (C-TST), symptom screening, chest X-rays, and bacteriological tests. The influencing factors of C-TST positivity were analyzed via generalized linear mixed models (GLMMs) and Boruta algorithm feature ranking. The TBI prevalence was estimated using WHO-recommended methods. Causal mediation analysis was performed to explore mediating variables contributing to association between altitude and TBI prevalence.ResultsThe estimated TBI prevalence in Tibet was 20.7% (95% CI 14.3%-33.0%). Residential altitude was the strongest predictor of C-TST positivity (aOR=0.53, p<0.001). The interaction analyses revealed significant modification effects of both smoking status (interaction p=0.0065) and BCG vaccination (interaction p=0.028) on the altitude-C-TST positivity association. Mediation analysis indicated that the observed inverse relationship between study site altitude and crude TBI prevalence was mediated by per capita land space (IE= -6.29e-05, p=0.04). The prevalence of TBI in very high-altitude (VHA) areas was 12.8%, approximately one-third of that in high-altitude (HA) areas (35.0%). Stratified analyses revealed distinct risk profiles - occupational exposures predominated in HA regions, whereas physiological factors (age, BMI, smoking) drove positivity in VHA areas.ConclusionOur results suggest that TB infection is significantly associated with altitude, necessitating accelerated research into plateau-specific disease mechanisms and the development of targeted public health strategies tailored to local socio-medical conditions. This integrated biological and socio-economic approach is essential to overcome the compounded vulnerabilities of high-altitude populations and ensure that China equitably achieves its goal of eliminating TB.